Perspective didactice în predarea limbii române la Universitatea de Stat din Arizona (Romanian Studies Today, 2024)
This article has a double purpose: on the one hand, I will present the main aspects related to teaching Romanian (as a heritage language or as a foreign language) at Arizona State University, SUA – principles, methods, perspectives, – and on the other hand, I will propose, based on my experience, a series of measures meant to improve the overall learning process at the preparatory year organized by numerous Romanian universities or at Romanian lectureships from outside Romania, with focus on distance learning, especially given the current pandemic context.
Keywords: Romanian as a heritage language; Romanian as a foreign language; teaching perspectives; distance learning and teaching